Retrieval of Critically Ill Adults Using Extracorporeal Membrane Oxygenation: The Nine-Year Experience in New South Wales. Issue 6 (November 2018) - Austin, D. E.; Burns, B.; Lowe, D.; Cartwright, B.; Clarke, A.; Dennis, M.; D'Souza, M.; Nathan, R.; Bannon, P. G.; Gattas, D.; Connellan, M.; Forrest, P.
In New South Wales, a coordinated extracorporeal membrane oxygenation (ECMO) retrieval program has been in operation since 2007. This study describes the characteristics and outcomes of patients transported by this service. We performed a retrospective observational study and included patients who were transported on ECMO to either of two adult tertiary referral hospitals in Sydney, New South Wales, between February 28, 2007 and February 29, 2016. One hundred and sixty-four ECMO-facilitated transports occurred, involving 160 patients. Of these, 118 patients (74%) were treated with veno-venous (VV) ECMO and 42 patients (26%) were treated with veno-arterial ECMO. The mean (standard deviation, SD) age was 40.4 (15.0) years. Seventy-seven transports (47%) occurred within metropolitan Sydney, 52 (32%) were from rural or regional areas within NSW, 17 (10%) were interstate transfers and 18 (11%) were international transfers. Transfers were by road (58%), fixed wing aircraft (27%) or helicopter (15%). No deaths occurred during transport. The median (interquartile range) duration of ECMO treatment was 8.9 (5.2–15.3) days. One hundred and nineteen patients (74%) were successfully weaned from ECMO and 109 (68%) survived to hospital discharge or transfer. In patients treated with VV ECMO, age, sequential organ failure assessment score, pre-existing immunosuppressive disease, pre-existing diabetes, renal failure requiring dialysis and failed prone positioning prior to ECMO were independently associated with increased mortality. ECMO-facilitated patient transport is feasible, safe, and results in acceptable short-term outcomes. The NSW ECMO Retrieval Service provides specialised support to patients with severe respiratory and cardiovascular illness, who may otherwise be too unstable to undergo inter-hospital transfer to access advanced cardiovascular and critical care services.